The influence of exposure, growth and maturation on injury risk in male academy football players - Johnson, D. M.; Cumming, S. P.; Bradley, B.; Williams, S. (Journal of Sports Sciences, 2022)
Adolescence is a period of increased injury risk in youth footballers; however, no studies have considered the influence of growth-related factors and exposure time upon injury risk. Forty-nine elite male youth footballers were prospectively monitored for growth, lower-limb growth, maturation, training volume and injury for one season. Generalised linear mixed-effects models were used to model growth rate, lower-limb growth rate, maturation, and smoothed week-to-week changes in exposure on time-loss injury risk. The relationship between growth rate and injury incidence was linear (P = 0.031) and injury burden was non-linear (P = 0.019). The relationship between lower-limb growth rate and injury incidence was linear and positive (P = 0.098). A non-linear relationship was observed between lower-limb growth rate and injury burden (P = 0.001). A non-linear relationship between Percentage of Predicted Adult Stature and both injury incidence and injury burden were found, with peak risk occurring at 92% and 95% , respectively. There was a positive linear relationship between week-to-week changeand injury incidence (P = 0.001), and a non-linear relationship between week-to-week change and injury burden (P = 0.01). Practitioners should monitor the timing and rate of the growth spurt and exposure time to identify players at greater injury risk.